Rumination time, activity index, and productive performance of Holstein and crossbred Holstein × jersey cows exposed to different temperature-humidity indexes - Kappes R.* (2022)
© 2022, The Author(s) under exclusive licence to International Society of Biometeorology.The aim of this study was to evaluate the rumination time, activity index, milk yield (MY), physicochemical milk characteristics, and physiological indicators of pure Holstein (H) and first (F1- ½ Holstein × Jersey) and second-generation (R1- ¾ Holstein × ¼ Jersey) of crossbred cows in a pasture-based system under the influence of different temperature–humidity indexes (THI). Twenty-two multiparous cows (H = 7, F1 = 5, and R1 = 10) were evaluated throughout 1-year period. Daily information on rumination time and activity index was obtained using the software HealthyCow24® and the daily THI was determined from data logger information. Weekly, MY, physicochemical milk characteristics, body weight, body condition score, and physiological indicators were evaluated. THI were grouped into six classes from safe (< 68) to emergency (≥ 84). Variance analyses were performed. There was no interaction between the genetic group and THI classes for any trait. The rumination time was longer for crossbred R1 and F1 cows than for Holstein cows. The activity index increased, and rumination time decreased as the THI classes increased. There was no difference in MY between the genetic groups, but crossbred cows showed higher milk fat and protein content. Our study indicated that the high THI increases the activity index and decreases the rumination time, MY, and the physicochemical quality of milk, BW, BCS, RF, and RT of the three genetic groups (H, F1, and R1).